Laterality of Ovulation and Presence of the Embryo Do Not Affect Uterine Horn Blood Flow During the First Month of Gestation in Llamas - Ratto, Marcelo H.; Urra, Felipe; Silva, Mauricio (Frontiers in Veterinary Science, 2020)
We determined if laterality of ovulation and intrauterine embryo location induces changes in the mesometrial/endometrial vascularization area (MEVA) between uterine horns, during the embryonic peri implantation phase in llamas. Adult, non-pregnant and non-lactating llamas (n=30) were subjected to daily ultrasound scanning of their ovaries. Llamas with a growing follicle ≥8 mm in diameter in the left (n=15) or right (n=15) ovary were assigned to mate with an adult fertile or vasectomized male. Power-doppler ultrasonography was used to determine the MEVA in a cross section of the middle segment of both uterine horns. MEVA was determined by off-line measurements using the ImageJ software. MEVA measurements were performed before mating (day 0) and on days 5, 10, 15, 20, 25 and 30 after mating in pregnant [llamas with left- (n=6) or right-sided (n=6) ovulations] and non pregnant [llamas with left- (n=6) or right-sided (n=6) ovulations] females. Ovulation was confirmed by the disappearance of a follicle (≥8 mm) detected previously. Pregnancy was confirmed by the presence of the embryo. MEVA was analyzed by one-way ANOVA for repeated measures using the MIXED Procedure in SAS. If significant (P≤ 0.05) main effects or interactions were detected, Tukey´s post-hoc test for multiple comparisons was used. Ovulation rate did not differ (P=0.4) between females mated to an intact or vasectomized male or between right- or left-sided ovulations. Three females mated to the intact and 3 to the vasectomized male did not ovulate and were excluded of the study. First observation of gestational sac and of embryo proper, were made exclusively in the left uterine horn, on day 15.8 3.8 and 22 2.7, and 16.7 2.6 and 27.5 2.8 for pregnant llamas ovulating in the right and left ovary respectively. Although the MEVA of both uterine horns was affected by time (P< 0.05), it was not affected by physiological status (pregnant vs non-pregnant; P= 0.9) or laterality of ovulation (P=0.4). Contrary to expectations, regardless of the laterality of ovulation, in pregnant llamas the left horn did not display a greater MEVA before or after embryo arrival, a trend that was observed during the first 30 days of gestation.